Change in mitochondrial capacity in elite triathletes, cyclists, and wrestlers over a training period of 28 days - Hannes Bossung; Christian Roth; Florian Netzer; Michael Behringer (European Journal of Applied Physiology, 2026)
Purpose This study investigated the change in mitochondrial capacity and V O 2 max in elite triathlon, cycling, and Greco-Roman wrestling athletes over a 28-day training period. Methods Sixteen elite athletes (23 ± 2.5 years; 176 ± 6 cm; 76 ± 8 kg; 65 ± 6.9 ml/min/kg) participated. Mitochondrial capacity was assessed before (pre) and after (post) a 28-day training period by measuring the increase in deoxygenated hemoglobin (HHb) in the m. vastus lateralis during three consecutive one-minute rapid cuff occlusion periods using near-infrared spectroscopy. V O 2 max was measured via a treadmill ramp test at the same time points. Results The analyses revealed significant differences between pre- and post-measurements, with significant improvements in the second (Δ τ 2 = − 3.4 ± 2.7 s, p = 0.001) and third (Δ τ 3 = − 5.0 ± 5.1 s, p = 0.006) occlusion period. Correlation analyses demonstrated a moderate negative relationship between the first occlusion tau ( τ ) rate and V O 2 max at pre-test ( r = − 0.58, p = 0.02) and an even stronger negative correlation at post-test ( r = − 0.62, p = 0.01). Within-subject analysis identified 14 athletes as responders. Conclusion The changes in τ rates indicate significant improvements in mitochondrial capacity over a period of 28 days in elite athletes, underscoring the utility of NIRS-derived τ rates for monitoring changes in elite athletes. Graphical abstract

Delineation of the adult phenotype of Coffin–Siris syndrome in 35 individuals - Ariane Schmetz; Hermann-Josef Lüdecke; Harald Surowy; Sugirtahn Sivalingam; Ange-Line Bruel; Roseline Caumes; Perrine Charles; Nicolas Chatron; Krystyna Chrzanowska; Marta Codina-Solà; Cindy Colson; Ivon Cuscó; et al. (Human Genetics, 2024)

New genetic evidence for involvement of the dopamine system in migraine with aura - Unda Todt; Christian Netzer; Mohammad Toliat; Axel Heinze; Ingrid Goebel; Peter Nürnberg; Hartmut Göbel; Jan Freudenberg; Christian Kubisch (Human Genetics, 2009)